Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/nu13041300
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Content of Docosahexaenoic Acid (DHA) of Donor Human Milk for Feeding Preterm Infants: A Comparison with Mother’s Own Milk at Different Stages of Lactation

Abstract: A cross-sectional single-center study was designed to compare the fatty acids profile, particularly docosahexaenoic acid (DHA) levels, between milk banking samples of donor human milk and mother’s own milk (MOM) for feeding preterm infants born before 32 weeks’ gestation. MOM samples from 118 mothers included colostrum (1–7 days after delivery), transitional milk (9–14 days), and mature milk (15–28 days and ≥29 days). In the n-3 polyunsaturated fatty acids (PUFAs) group, the levels of α-linolenic acid (C18:3 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Other studies have consistently demonstrated the need to add n-3 PUFAs for preterm infant formulas to obtain fatty acid profiles comparable to infants receiving human milk [ 39 , 40 ]. In a previous study of our group, donor human milk had an inadequate content of DHA for feeding preterm infants, so that milk banking fortified with DHA would ensure adequate DHA levels [ 22 ]. Also, DHA supply dose in preterm infants dependently increased plasma DHA levels [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have consistently demonstrated the need to add n-3 PUFAs for preterm infant formulas to obtain fatty acid profiles comparable to infants receiving human milk [ 39 , 40 ]. In a previous study of our group, donor human milk had an inadequate content of DHA for feeding preterm infants, so that milk banking fortified with DHA would ensure adequate DHA levels [ 22 ]. Also, DHA supply dose in preterm infants dependently increased plasma DHA levels [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infants born preterm are especially dependent on an adequate postnatal nutritional supply of DHA, but this is difficult to achieve for different reasons. There is a deficient lipid profile based on analysis of fatty acid composition in food sources for premature infants, plasma or cord blood samples [ 22 , 23 , 24 ], a need to rely on parenteral nutrition particularly in neonates admitted to the neonatal intensive care unit (NICU), the difficulties of mothers in producing enough breast milk volume for exclusive enteral feeding, and the composition of milk banks based on pooled mature milk with deficient DHA levels. Moreover, the recommended minimal intake of 450 g/day of DHA for pregnant and lactating women is rarely achieved unless there is an increase in DHA intake through fish consumption or nutritional supplements with high-dose DHA while breastfeeding [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatty acids (FAs) play an important role in energy metabolism and compose fundamental structures through various types of lipids [ 1 ]. Important among these structures are n -3 (omega-3) polyunsaturated fatty acids (PUFAs), which are involved neurodevelopment, immune function, cellular signaling processes, angiogenesis, and inflammatory response [ 2 , 3 , 4 ], playing a crucial role in children’s growth, development, and function. Docosahexaenoic acid (DHA, C22:6 n -3) is the predominant n -3 PUFA, making up over 90% of the n -3 PUFAs in the brain and 10–20% of its total lipids [ 5 ].…”
Section: Introductionmentioning
confidence: 99%